Ecdysteroid hormones in molting cycle of mud crab (Scylla paramamosain Estampador, 1950) - Techa, Sirinart; Jaiman, Peeradet Jaiman; Aiemsomboon, Kornrawee (Agriculture and Natural Resources, 2026)
Importance of the work: Understanding ecdysteroid hormones and their role in the molting cycle of the mud crab (Scylla paramamosain Estampador, 1950) is vital for advancing commercial aquaculture, particularly for optimizing soft-shell crab production and ensuring sustainable farming practices. Objectives: To investigate the ecdysteroid derivatives—20-hydroxyecdysone (20-HE) and ponasterone A (PoA)—in the molting cycle of the mud crab (S. paramamosain). Materials and Methods: Crabs (S. paramamosain) were reared in a recirculating system. A hemolymph sample was collected from each crab. Ecdysteroid hormones—ecdysone (E), 20-HE, PoA—were measured using high-performance liquid chromatography (HPLC) and enzyme immunoassay (EIA) and analyzed based on analysis of variance and Student’s t test. Results: HPLC identified PoA as the primary ecdysteroid (33.59–675.06 ng/mL); however, E and 20-HE were undetectable using HPLC, while EIA detected 20-HE, (69.01–259.27 ng/mL). The PoA levels were significantly (p < 0.001) higher in the premolt stage than the intermolt stage. In addition, the 20-HE levels were significantly (p < 0.05) higher during premolt. The resulting PoA:20-HE ratios were approximately 1:1 in the intermolt stage and increased to approximately 2:1 in the premolt stage. Main finding: PoA was identified and reported for the first time as the primary molting hormone in S. paramamosain, providing essential knowledge for optimizing aquaculture.